경사진 램프를 통한 장축 화물의 선적 궤적 생성 - 박재엽(Jaeyeob Bak); 김성준(Seongjun Kim); 만예동(Ruidong Man); 윤재득(Jaedeuk Yun); 정융호(Yoongho Jung) (한국CDE학회 논문집, 2020)
Roll-on and roll-off (Ro-Ro) ship is the most economical transporting method for large freights such as train, helicopter, and aircraft body. To ship a large freight to a designated location on deck of Ro-Ro ship, tractor is used to pull a trailer with a connecting link of goose neck shape, on which the freight is secured. When the freight is long enough, the trajectory of trailer is not same as that of trailer and is a three dimensional path, which can cause any collision with ramp, gate, and obstacles in the deck. This research proposes a method of calculating possible trajectories to drive a tractor, along which does not cause any collision. Assuming reasonably low speed of a tractor, the proposed method generates possible tractor paths based on Bezier curve to calculate the trailer path considering tilt of tractor and trailer when they go up the inclined ramp. Finally, it calculates the best three paths without any collision in order of priority with minimum shipping time. The proposed method can be useful for the transport company to determine the shipping possibility as well as to generate driving order for a tractor driver. KCI Citation Count: 0